Polymer Matrix-Based Piezoelectric Composite for Structural Health Monitoring - Sakamoto, Walter Katsumi [UNESP]; Higuti, Ricardo Tokio; Crivelini, Evelyn Brazoloto [UNESP]; Nagashima, Haraldo Naoyuki [UNESP]; IEEE (Ieee, 2013)
Structural health monitoring (SHM) refers to the procedure of assessing the structure conditions continuously so it is an alternative to conventional nondestructive evaluation (NDE) techniques [1]. With the growing developments in sensor technology acoustic emission (AE) technology has been attracting attention in SHM applications. AE are characterized by waves produced by the sudden internal stress redistribution caused by the changes in the internal structure, such as fatigue, crack growth, corrosion, etc. Piezoelectric materials such as Lead Zirconate Titanate (PZT) ceramic have been widely used as sensor due to its high electromechanical coupling factor and piezoelectric d coefficients. Because of the poor mechanical characteristic and the lack in the formability of the ceramic, polymer matrix-based piezoelectric composites have been studied in the last decade in order to obtain better properties in comparison with a single phase material. In this study a composite film made of polyurethane (PU) and PZT ceramic particles partially recovered with polyaniline (PAni) was characterized and used as sensor for AE detection. Preliminary results indicate that the presence of a semiconductor polymer (PAni) recovering the ceramic particles, make the poling process easier and less time consuming. Also, it is possible to observe that there is a great potential to use such type of composite as sensor for structure health monitoring.
Keywords: component; composite; nondestructive evaluation; acoustic emission; PZT